Calibration of concomitant field offsets using phase contrast MRI for asymmetric gradient coils. Issue 1 (21st September 2022) - Abad, Nastaren; Lee, Seung‐Kyun; Ajala, Afis; In, Myung‐Ho; Frigo, Louis M.; Bhushan, Chitresh; Morris, H. Douglas; Hua, Yihe; Ho, Vincent B.; Bernstein, Matt A.; Foo, Thomas K. F.
Abstract : Purpose: Asymmetric gradient coils introduce zeroth‐ and first‐order concomitant field terms, in addition to higher‐order terms common to both asymmetric and symmetric gradients. Salient to compensation strategies is the accurate calibration of the concomitant field spatial offset parameters for asymmetric coils. A method that allows for one‐time calibration of the offset parameters is described. Theory and Methods: A modified phase contrast pulse sequence with single‐sided bipolar flow encoding is proposed to calibrate the offsets for asymmetric, transverse gradient coils. By fitting the measured phase offsets to different gradient amplitudes, the spatial offsets were calculated by fitting the phase variation. This was used for calibrating real‐time pre‐emphasis compensation of the zeroth‐ and first‐order concomitant fields. Results: Image quality improvement with the proposed corrections was demonstrated in phantom and healthy volunteers with non‐Cartesian and Cartesian trajectory acquisitions. Concomitant field compensation using the calibrated offsets resulted in a residual phase error <3% at the highest gradient amplitude and demonstrated substantial reduction of image blur and slice position/selection artifacts. Conclusions: The proposed implementation provides an accurate method for calibrating spatial offsets that can be used for real‐time concomitant field compensation of zeroth and first‐order terms, substantially reducing artifacts without retrospective correction or sequence specific waveform modifications.